INFLUENCE OF ISOINERTIAL EXERCISES ON LOWER LIMB POWER AND STABILITY OF VOLLEYBALL PLAYERS - REITMAYER, Hans-Eric; MONEA , Dan (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
Introduction: Flywheel training devices have initially been used as means of astronaut conditioning in outer space, during long missions. The system uses a rotating disc to store the energy during the concentric phase of the movement and converts it to resistance during the eccentric phase. The inertia of the flywheel offers the load of the exercise performed. Later, these devices started being used in injury rehabilitation and performance training. Objective: The objective of the study was to measure the effect of isoinertial exercises using a flywheel training device on lower limb power and stability. Also, we wanted to verify if a positive correlation can be found between force, power and stability. Methods: 15 female volleyball players were included in the study (N=15). Throughout 4 months, the subjects trained twice a week using the flywheel device. Initial and final tests were performed using OptoJump, Y balance test and the device’s own measuring system. The measured parameters were average power, average force, jump height and composite reach distance index. Results: Significant improvement have been found between the initial and final results for power, force, jump height and composite reach distance index p<.01. Conclusions: A flywheel isoinertial training device can be seen as a viable alternative for power and stability development for volleyball players.